Portfolio Limits : Pension Investment Restrictions Compromise Fund Performance - World Bank (World Bank, Washington, DC, 2012)
The value of funded pensions can depend critically on the funds' investment performance. To try and protect people's savings, governments often regulate pension funds strictly, particularly when contributions are mandatory. For example, the new funded pension systems in Latin America and Eastern Europe are more stringently regulated than private pensions in OECD countries, which are mainly voluntary. While these pension fund regulations take three different forms, this briefing focuses on one of these: quantitative restrictions on pension funds' portfolios. Quantitative restrictions on the share of particular types of assets held by the fund limit the dispersion of outcomes, particularly for defined contribution schemes. In most mandatory schemes, this leads to a 'single portfolio' environment where members of the scheme are forced to hold basically the same portfolio. Most common are limits on risky assets such as shares and corporate bonds. Often, foreign investments are curtailed. This review includes a look at the adverse effects of portfolio limits, and argues for relaxing investment rules so that pension funds can reap the benefits from international diversification.